Quality Control Guidelines for BAL9141 (Ro 63-9141), an Investigational Cephalosporin, When Reference MIC and Standardized Disk Diffusion Susceptibility Test Methods Are Used - Anderegg, T. R. (American Society for Microbiology, 2004)
BAL9141 is a novel cephalosporin with a broad spectrum of activity, including activity against methicillin-resistant staphylococci. This multicenter study was performed to establish quality control (QC) guidelines for susceptibility testing of BAL9141 in phase 3 clinical trials and after U.S. Food and Drug Administration approval. The proposed 3 or 4 log(2) dilution MIC ranges encompass 97.8 to 100.0% of reported results, while the proposed 7- to 9-mm-zone-diameter QC ranges included 95.2 to 99.4% of the participant-reported disk diffusion results.